Immune Thrombocytopenic Purpura in Pregnancy- A Prospective Observational Study in a Tertiary Care Centre - Parveen, Tabassum; Begum, Firoza; Akhter, Nahreen; Sultana, Nigar; Nahar, Khairun (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Objectives: Immune thrombocytopenic purpura (ITP) in pregnancy necessitates management of two patients, the mother and the newborn. Complications like maternal bleeding, fetal and neonatal thrombocytopenia demands appropriate and timely therapy. This prospective observational study was designed to explore and summarize the current approach to the investigation, diagnosis, management and outcome of ITP in pregnancy. Materials and Methods: Women with ITP admitted in the Fetomaternal Medicine Department of Bangabandhu Sheikh Mujib Medical University (BSMMU) from 2009 -2017, were included in the study. Total number of high risk pregnancy during that period were 7704 among them 20 cases were pregnancy with Immune Thrombocytopenic Purpura (ITP). Patients were managed under joint supervision of the fetomaternal medicine specialist and the hematologist. Prednisolone was considered as a first line drug in management protocol. Platelet transfusion was considered if there were symptoms or count <20X109/L at any stage of pregnancy or <50 X109 / L in late pregnancy without symptoms. Platelet count of newborn was performed at birth and repeated on day four and count<150X109/L was considered as neonatal thrombocytopenia. Results: Frequency of ITP among high risk patients was found 2.5/1000 live birth, most were preexisting (75%). Almost all cases (95%) were treated with prednisolone. Commonest clinical presentations were gum bleeding (70 %) and purpuric rashes (60%). Though during pregnancy, severe thrombocytopenia (<50 X109/L) was found in 7 patients (35%) but none was at the time of delivery, as drugs and/or platelet transfusion was considered to make delivery process safe. Platelet transfusion needed in 77.7% cases in a range of 1-75 units. Primary PPH noted in 3 cases (17%), increased bleeding during surgery in 5 patients (33%) and one patient needed ICU support. Neonatal thrombocytopenia noted in 5 cases (28%). Though 2 of the neonates needed NICU admission but none needed platelet transfusion and all the babies were discharged healthy. Conclusion: This study documents that pregnancy with ITP need close monitoring, require agents to raise the platelet count and repeated platelet transfusion to maintain reasonable safe platelet count. There are chances of PPH, capillary oozing during surgery. However good outcome is possible for most women, fetus and neonates with appropriate and timely therapy. Bangladesh J Obstet Gynaecol, 2019; Vol. 34(1): 15-21